P011 Development of an online behavioural sleep intervention for parents of children with epilepsy, for use in the CASTLE (changing agendas on sleep, treatment and learning in epilepsy) study clinical trial. (19th November 2019) - Wiggs, Luci; Cook, Georgia; Hiscock, Harriet; Gringras, Paul
Abstract : Introduction: Many of the same sleep problems experienced by children with epilepsy (CWE) are commonly seen in typically developing (TD) children. Behavioural sleep interventions (BSI) are commonly and successfully used to treat these sleep problems in TD children and in some neurodevelopmental disorder populations. BSI should therefore be effective in CWE. However, there are special seizure-related considerations for CWE and their parents which may need to be acknowledged in any BSI for this population. Through Patient and Public Involvement (PPI), this project aimed to understand parents' opinions and experiences around their child's sleep and sleep interventions in order to tailor a BSI for use in the CASTLE (Changing Agendas on Sleep, Treatment and Learning in Epilepsy) study clinical trial with CWE. Method: Semi-structured interviews were conducted with 10 mothers of CWE and 3 CWE recruited via online adverts on epilepsy relevant websites. A thematic analysis was conducted on the interview data. Results: Several strong themes were apparent including that i) families felt in need of information, support and help with sleep, ii) parents valued other parents' experience/understanding (over professionals' advice), iii) any intervention needed to be personalised and non-prescriptive, and iv) parents' concerns needed to be included. Two theory-driven BSIs, used in evidence-based level 1 studies, were adapted to incorporate parents' requirements, developed into an online intervention (CASTLE Online Sleep Intervention or COSI) for parents of CWE and refined following parental evaluation (via online questionnaire built into COSI) until 100% approval from parents was reached. Discussion: Adaptations and additions to content and delivery format were necessary to ensure that COSI best met parents' needs; the final version will be used in the CASTLE study clinical trial (http://castlestudy.org.uk/). It is hoped that the use of evidence-based techniques delivered with consideration of factors identified through PPI, can increase parent-engagement and optimise effectiveness.